THE INFLUENCE OF SERVICE QUALITY (IN THE INSURANCE DIMENSION) THROUGH BUDGET FUNDS ON UMRAH PILGRIMAGE SATISFACTION - Rahayu Yonita; Yuda Septian Kurniawan; Syafri Yanto (Jurnal Aghniya, 2025)
This study aims to determine the effect of service quality through the Umrah fund bailout product on the satisfaction of the AET Travel congregation (Penjuru Wisata Negeri  cabang Area V) This study used a descriptive analysis approach with quantitative research methods, the subject and object in this study were the congregation of The AET Travel Bengkulu who has gone on Umrah using Umrah bailout funds and obtained 33 samples who distributed questionnaires. During the study, the researcher encountered obstacles, namely limited research time and the willingness of respondents to fill out the questionnaire so that they were willing to be used as a sample of 33 respondents. The analytical tools used were validity, reliability, classical assumption tests, simple linear regression tests, and hypothesis tests which were then analyzed using SPSS 25.0 program, the results in this study showed that there was a significant positive influence based on the results of simple linear regression with a regression coefficient value of 2.863 with a sig of 0.007 which is smaller than 0.05.